Ácido protocatecúico e seus ésteres alquílicos: propriedades antioxidantes e seus efeitos no metabolismo oxidativo de leucócitos - Faria, Carolina Maria Quinello Gomes de [UNESP] (2014)
Nicotinamide adenine dinucleotide phosphate (NADPH) oxidases are multienzymatic complexes associated to the cell membranes whose main function is to catalyze the reduction of molecular oxygen to superoxide (O2 •-). In leukocytes, this is the primary mechanism through which these cells produce reactive oxygen species (ROS), which are involved in both the innate immune defense mechanisms and deleterious oxidative processes, which characterizes many chronic inflammatory diseases. In this thesis we present the results and proposed mechanism of inhibition of the NADPH oxidase complex by a group of synthetic alkyl esters derived from protocatechuic acid, a phenolic acid present in many plants with detached antiradical capacity. Our hypothesis was that the increase in hydrophobicity caused by esterification of protocatechuic acid could facilitate their access to the cell membrane and thereby alter their biological effects. This hypothesis was confirmed, since not only its anti-radical activity was increased (in vitro models), but also caused a significant improvement in their ability to inhibit NADPH oxidase complex in leukocytes (ex vivo models). This effect has spread to ROS derived from superoxide anion and produced by leukocytes such as hydrogen peroxide and hypochlorous acid, without altering their phagocytic capacity. It must be emphasize that the observed cellular effects were not due to simple suppressive action on ROS, but effective inhibition of its formation, which was demonstrated by the various control experiments. The esterification of protocatechuic acid also caused improvement in their capacity as inhibitor of TNF-a and IL-10 production by peripheral blood mononuclear leukocytes. Considering the low toxicity and low cost of synthesis of these esters, we suggest that they could be used in in vivo models as promising anti-inflammatory ...